Evaluation of the bacterial diversity of Spanish-type chorizo during the ripening process using high-throughput sequencing and physicochemical characterization. (April 2019) - Juárez-Castelán, Carmen; García-Cano, Israel; Escobar-Zepeda, Alejandra; Azaola-Espinosa, Alejandro; Álvarez-Cisneros, Yenizey; Ponce-Alquicira, Edith
Abstract: Spanish-type chorizo is a fermented meat product that is highly appreciated by consumers. The physicochemical properties (pH, water activity (aw ), total acidity (TA), and malonaldehyde content) were evaluated in the initial meat batter and at different ripening stages. Bacterial diversity and dynamics were also examined using high-throughput sequencing. A decrease in pH and aw was observed during ripening, while the TA and malonaldehyde contents increased significantly. This data correlated with the changes in lactic acid bacteria and enterobacteria populations. Total bacterial diversity in the initial samples was represented by Proteobacteria (44%) and Firmicutes (55%) phyla, where Pseudomonas (23%), Streptococcus (21%), Acinetobacter (14%), Bacillus (13%), and Brochothrix (11%) were the most abundant genera. In contrast, Firmicutes reached the highest frequency (~89%), with Lactobacillus and Streptococcus being the most represented at the end of ripening. Lactobacillus sakei, Pediococcus acidilactici, and Weissella thailandensis were identified by 16S rRNA gene analysis and were considered potentially responsible for the stability, microbiological safety, and sensory characteristics of this product. Highlights: Physicochemical changes were correlated with bacterial growth. Using high-throughput DNA sequencing technology it was recovered ~71% of total diversity. During ripening process predominant phyla were Firmicutes and Proteobacteria. Lactobacillus and Streptococcus genera were the most abundant during ripening process. L. sakei was the dominant specie and it was confirmed by 16S rDNA sequencing.